Validity and reliability of the Finnish version of the Foot and ankle ability measure - Liedes, Joonas (fi=Turun yliopisto|en=University of Turku|, 2018)
Background This study was designed to adapt the Foot and ankle ability measure FAAM to the Finnish language (FAAM-Fi) and to assess its validity and reliability. Methods Cross-cultural adaptation was carried out according to the method used by the Outcomes Committee of the American Association of Orthopedic Surgeons. The study population completed the FAAM-Fi and a health quality of life instrument 15D three times. The test-retest agreement was assessed by calculating an agreement number for each question. Construct validity was assessed between FAAM-Fi and 15D. Convergent validity was examined by assessing the correlation between the FAAM-Fi and 15D physical component. Divergent validity was examined by assessing the correlation between the FAAM-Fi and the 15D mental component summary. Results Partial agreement varied from 89% to 100%. Spearman’s correlation coefficient between 15D and FAAM subscales were 0.51, 0.56 and 0.52 (p<0.0001). Spearman’s correlation coefficient at baseline between the replies to the mobility question and FAAM-Fi subscales were 0.53, 0.54 and 0.60 (p<0.0001). None of the FAAM-Fi scores correlated with the 15D mental component summary at any time point (p=0.075-0.633). Conclusion FAAM-Fi was translated and cross-culturally adapted according recommendations and it is valid and reliable for self-reporting of outcomes in connection with foot and ankle disorders for Finnish speaking people in the Finnish culture.